SIMULTANEOUS ADSORPTION OF TETRACYCLINE AND AMOXICILLIN BY CLADOPHORA AND SPIRULINA ALGAE BIOMASS - Abd, I. N.; Mohammed-Ridha, M. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Adsorption studies were performed at different initial Tetracycline (TC) and Amoxicillin (AMO) concentration, different biomass dosage and type, contact time, agitation speed, and initial pH. In the batch mode were investigated. The optimum pH of solutions is 6.5 for TC and 5 for AMO, agitation speed 200 rpm and concentration 50 ppm. The results in FTIR showed that there were -OH and amides (N-H) and other functional groups on the surface of Cladophora and Spirulina algae. The equilibrium isotherm data were modeled with Freundlich, Temkin, and Langmuir isotherm models. The data best fitted with the Langmuir model. The maximal adsorption capacity from the Langmuir model was (9.86, 20. 5 mg/g) for TC and (7.89, 17.4 mg/g) for AMO on Cladophora and Spirulina algae, respectively. Finally, the pseudo-second-order kinetic model was best fitted the experimental kinetic data of TC and AMO onto Cladophora and Spirulina algae biomass with a high coefficient of determination between 0.97 and 0.99. Cladophora and Spirulina algae, low-cost and eco-friendly adsorbents, can be used to adsorb the TC and AMO from the solution.